Deglaciation and weathering of Larsemann Hills, East Antarctica - Kiernan, K; Gore, DB; Fink, D; White, DA; McConnell, A; Sigurdsson, IA (Antarctic Science, 2009)
In situ cosmogenic 10Be exposure dating, radiocarbon determinations, salt and sediment geochemistry, and rock weathering observations indicate that parts of Larsemann Hills, East Antarctica have been subaerially exposed throughout much of the last glacial cycle, with the last glaciation occurring prior to 100 ka bp. Salt-enhanced subaerial weathering, coupled with a paucity of glacial erratics, made exposure age dating challenging. Rapid subaerial surface lowering in some places means that some exposure ages may underestimate the true age of deglaciation. Despite this uncertainty, the data are consistent with the absence of overriding by a thick ice sheet during the Last Glacial Maximum 2018 ka bp.